SCLEROCYSTIC OVARIES: CURRENT APPROACHES TO THE PROBLEM - A. G. Solopova; A. D. Makatsariya; A. E. Solopova; O. V. Nikiforova (Акушерство, гинекология и репродукция, 2017)
The review addresses the current concepts on polycystic ovary syndrome (PCOS), including the key elements of PCOS etiology, pathogenesis, and epidemiology. The major clinical manifestations, diagnostic standards at early and later stages, treatment regimens, and novel research are also discussed. Despite a lot of research conducted in Russia and elsewhere, many aspects of PCOS remain to be clarified. It is hoped that by introducing recent innovations we can improve medical and instrumental diagnostics, treatment and prevention of PCOS.